PENGARUH FAKTOR PREDISPOSING, ENABLING DAN REINFORCING TERHADAP PEMBERIAN IMUNISASI HEPATITIS B PADA BAYI DI PUSKESMAS BAGAN BATU KECAMATAN BAGAN SINEMBAH KABUPATEN ROKAN HILIR - Reni Agustina Harahap, SST., M.Kes (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2016)
ABSTRACTImmunization is one of the preventive measures to prevent the disease by giving immunity to be performed continuously and thorough, and conducted according to standars so as to provide protection of health and break the chain of transmission. The results of this study showed that the variables thet influence the provision of Hepatitis B immunization is attitude, facilities , the role of health workers and the support of community leaders. Suggested to the Health Center Bagan Batu to socialize and improve their knowledge in terms of public health through health promotion efforts in the form of social support, namely improving the quality of health promotion efforts in the form of social support, namely improving the quality of health education and the provision of media sorces of health information about the spread of immunization will be able to reach the right target mothers located in the village of Rokan Hilir regencies. Keywords: Predisposing, Enabling and Reinforcing, Hepatitis B Immunization